Dynamic Effect of Flow on Impulsive Consumption: Evidence from Southeast Asian Live Streaming Platforms - Pradeep, Paraman; Sanmugam, Annamalah; Peter, Vlachos; Selim, Ahmed; Arunnan, Balasubramaniam; Baharudin, Kadir; Murali, Raman; Wong, Chee Hoo (Molecular Diversity Preservation International (MDPI), 2022)
The impulsive live streaming consumption intentions of the Southeast Asian market are examined in this study. Online live streaming transactions, a new form of social media, are becoming popular due to their real-time communication and innovative business concept. Though little attention has been dedicated to it, a theoretical knowledge of Live Streaming Transaction (LST) is crucial given its broad application and unique features. The analysis of 8613 respondents from Southeast Asia in this study, based on flow, temperament, and personality theories, offers fresh perspectives on the mediating role of flow and the moderating effect of temperament in a cross-national setting. Cluster sampling was used to construct a mixed-method conditional indirect effects model. Since introverted temperament types look for voices that echo within them, our findings revealed that LSTs are more intriguing to this market segment. Theoretical and practical elements, as well as implications for future directions, are presented.